Study of Antimicrobial Activity of ZnO Nanoparticles Dopped Natural Hydroxyapatites - Karki, Dirgha Raj; Bhujel, Sushant; Parajuli, Kshama; Pant, Ramesh Raj; Sharma, Motee Lal (Journal of Nepal Chemical Society, 2024)
Bone replacements and repairs often encounter infections from diverse microbes, necessitating costly and painful secondary surgeries and treatments. Developing antimicrobial bone implants is crucial to mitigate these complications and enhance regeneration. Moreover, the biological synthesis of hydroxyapatite (Ca10(PO₄)6(OH)2, a primary component of human bone, presents advantages over chemically synthesized alternatives due to lower impurity and cost. This study focuses on synthesizing hydroxyapatite powders from buffalo and goat femoral bones, with the incorporation of ZnO nanoparticles. Analyzed via XRD and FTIR, the prepared powder exhibited potent antimicrobial properties against various bacterial strains. Specifically, the hydroxyapatite powder doped with ZnO nanoparticles displayed superior antimicrobial activity. Consequently, this synthesized material holds significant promise for applications in bone tissue engineering and related fields.